Indian Tea Scenario and its opportunity in the global market - Mr.Diganta Kumar Bora,; Dr.Rana Pratap Bhuyan,; Mr. Manuranjan Gogoi,; Dr.Srstisri Upadhyaya, (IJRDO - Journal of Social Science and Humanities Research, 2020)
India is the second largest tea producing country in the world after China having plantation area of about 6.36 lakh hectares. Highest ever production of tea was recorded in 2018 with a staggering figure of 1338.63 million kg. However, productivity of tea in the country is 2103 Kg made tea per ha which is 4 % less than the year 2016. India ranked fourth in terms of tea exports, which reached 254.50 million Kg in 2018-19. Import of tea reached to 24.22 million kg which is highest in recent time. Average price of all categories of tea in all India auction sale was Rs. 140.26 which is also in increasing trend. Tea has become a trendy product for young people who love to drink it in the sophisticated environment of specialty teashops and exclusive restaurants, hotels and cafés. Promoting health benefits to boost the demand is the need of the hour.